EMPIRICAL STUDY OF TRANFER PRICING ON CONSUMPTION COMPANIES ON THE INDONESIA STOCK EXCHANGE - Mamay Komarudin; Grace Citra Dewi (SEAN Institute, 2022)
The purpose of this study is to analyze the effect of good corporate governance (GCG) on transfer pricing; analyze the effect of tunneling incentives on transfer pricing, the effect of intangible assets on transfer pricing, and the effect of profitability on transfer pricing . This type of research is explanatory research. The population of this study is multinational companies in the consumption industry listed on the Indonesia Stock Exchange (IDX). The method analysis of multiple linear analysis to search for its regression equation. The data analysis results show that Good Cooporate Goverment (GCG) has a positive and significant effect on the company's decision to carry out transfer pricing. Tunneling Incentive (TNC) positively and significantly affects the company's decision to carry out transfer pricing. Intangible Assets do not have a positive and insignificant effect on the company's decision to transfer pricing. Profitability does not have a positive effect on the company's decision to transfer pricing